Carrier for electrostatic charge image development, electrostatic charge image developer, process cartridge, image forming apparatus, and image forming method

JP2025026178APending Publication Date: 2025-02-21FUJIFILM BUSINESS INNOVATION CORP
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
JP2023131601
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-08-10
Publication Date
2025-02-21

AI Technical Summary

Benefits of technology

【0007】 <1>に係る発明によれば、樹脂被覆層又は内部空隙に配置された樹脂組成物が無機粒子を含有しない場合に比べ、高温高湿下において画像密度の高い画像を長期にわたって連続で形成したときにおける、像保持体への静電荷像現像用キャリアの付着が抑制される静電荷像現像用キャリアが提供される。 <2>に係る発明によれば、面積比率Aが10%未満若しくは50%超え、又は面積比率A≦面積比率Bである場合に比べ、高温高湿下において画像密度の高い画像を長期にわたって連続で形成したときにおける、像保持体への静電荷像現像用キャリアの付着が抑制される静電荷像現像用キャリアが提供される。 <3>に係る発明によれば、面積比率Bが面積比率Aの0.05倍未満又は0.3倍超えである場合に比べ、高温高湿下において画像密度の高い画像を長期にわたって連続で形成したときにおける、像保持体への静電荷像現像用キャリアの付着が抑制される静電荷像現像用キャリアが提供される。 <4>に係る発明によれば、磁性粒子の内部空隙率が2%未満又は10%超えである場合に比べ、高温高湿下において画像密度の高い画像を長期にわたって連続で形成したときにおける、像保持体への静電荷像現像用キャリアの付着が抑制される静電荷像現像用キャリアが提供される。 <5>に係る発明によれば、無機粒子の個数平均粒径が5nm未満又は90nm超えである場合に比べ、高温高湿下において画像密度の高い画像を長期にわたって連続で形成したときにおける、像保持体への静電荷像現像用キャリアの付着が抑制される静電荷像現像用キャリアが提供される。 <6>に係る発明によれば、無機粒子がアルミナ粒子のみからなる場合に比べ、高温高湿下において画像密度の高い画像を長期にわたって連続で形成したときにおける、画像濃度変動が抑制される静電荷像現像用キャリアが提供される。 <7>、<8>、<9>、又は<10>に係る発明によれば、樹脂被覆層又は内部空隙に配置された樹脂組成物が無機粒子を含有しない静電荷像現像用キャリアを適用した場合に比べ、高温高湿下において画像密度の高い画像を長期にわたって連続で形成したときにおける、像保持体への静電荷像現像用キャリアの付着が抑制される静電荷像現像剤、プロセスカートリッジ、画像形成装置、又は画像形成方法が提供される。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025026178000004
    Figure 2025026178000004
  • Figure 2025026178000005
    Figure 2025026178000005
  • Figure 2025026178000006
    Figure 2025026178000006
Patent Text Reader

Abstract

To provide a carrier for electrostatic charge image development that can be prevented from being attached to an image holding body when images with high image density are formed continuously for a long period under high temperature and high humidity.SOLUTION: A carrier for electrostatic charge image development has: a magnetic particle having an internal gap; a resin coating layer covering the magnetic particle and containing a resin and inorganic particles; and a resin composition arranged in at least part of the internal gap and containing the resin and inorganic particles.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to an electrostatic image developing carrier, an electrostatic image developer, a process cartridge, an image forming apparatus, and an image forming method. [Background technology]

[0002] Patent Document 1 describes a composite material made of ferrite particles, having a specific pore volume, an average internal void area in a specific range, and a void area of ​​20 μm 2 The above-mentioned carrier for electrophotographic development is disclosed in which the surface of a carrier core material having an internal void ratio of 1.8% or less is coated with a resin.

[0003] Patent Document 2 discloses a carrier for developing an electrostatic latent image, which comprises a core particle and a resin coating layer in which conductive fine particles are dispersed, and The carrier has an average particle size of 25 to 60 μm and an average circularity of 0.975 or more, and the BET specific surface area of ​​the core particles is 0.1 to 0.3 m. 2 / g and an internal porosity of 10% or less. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] JP 2019-061188 A [Patent Document 2] JP 2007-058124 A Summary of the Invention [Problem to be solved by the invention]

[0005] The object of the present invention is to provide a carrier for developing electrostatic images, which is suppressed from adhering to an image holder when images with high image density are continuously formed over a long period of time under high temperature and high humidity conditions, as compared to a case in which the resin composition disposed in the resin coating layer or the internal voids does not contain inorganic particles. [Means for solving the problem]

[0006] Means for solving the above problems include the following aspects. <1> Magnetic particles having internal voids; a resin coating layer that coats the magnetic particles and contains a resin and inorganic particles; A resin composition disposed in at least a portion of the internal void and containing a resin and inorganic particles; A carrier for developing electrostatic images comprising: <2> In a cross section of the resin coating layer, a ratio of a total area of ​​the inorganic particles contained in the resin coating layer to a total area of ​​the resin coating layer is defined as an area ratio A, and in a cross section of the resin composition, a ratio of a total area of ​​the inorganic particles contained in the resin composition to a total area of ​​the resin composition is defined as an area ratio B. The area ratio A is 10% or more and 50% or less, and the area ratio A is greater than the area ratio B. <1> 2. The electrostatic image developing carrier according to claim 1 . <3> The area ratio B is 0.05 to 0.3 times the area ratio A. <2> 2. The electrostatic image developing carrier according to claim 1 . <4> The internal porosity of the magnetic particles is 2% or more and 10% or less. <1> ~ <3> 10. The electrostatic image developing carrier according to claim 9, <5> The number average particle size of the inorganic particles is 5 nm or more and 90 nm or less. <1> ~ <4> 10. The electrostatic image developing carrier according to claim 9, <6> The inorganic particles include silica particles. <1> ~ <5> 10. The electrostatic image developing carrier according to claim 9, <7> a toner for developing an electrostatic image; <1> ~ <6> 10. The electrostatic image developing carrier according to claim 9, 13. An electrostatic image developer comprising: <8> <7> and a developing device that contains the electrostatic image developer according to claim 1 and develops an electrostatic image formed on a surface of an image carrier into a toner image by using the electrostatic image developer, A process cartridge that is detachably attached to an image forming apparatus. <9> An image carrier; a charging device for charging the surface of the image carrier; an electrostatic image forming device for forming an electrostatic image on the charged surface of the image carrier; <7> a developing device that contains the electrostatic image developer according to claim 1 and develops the electrostatic image formed on the surface of the image carrier into a toner image by using the electrostatic image developer; a transfer device for transferring the toner image formed on the surface of the image carrier to a surface of a recording medium; a fixing device for fixing the toner image transferred onto the surface of the recording medium; An image forming apparatus comprising: <10> a charging step of charging a surface of an image carrier; an electrostatic image forming step of forming an electrostatic image on the charged surface of the image carrier; <7> a developing step of developing the electrostatic image formed on the surface of the image carrier into a toner image by using the electrostatic image developer according to claim 1; a transfer step of transferring the toner image formed on the surface of the image carrier onto a surface of a recording medium; a fixing step of fixing the toner image transferred onto the surface of the recording medium; The image forming method according to claim 1, Effect of the Invention

[0007] <1> According to the invention, there is provided a carrier for developing electrostatic images in which adhesion of the carrier for developing electrostatic images to an image holder is suppressed when images with high image density are continuously formed over a long period of time under high temperature and high humidity conditions, compared to when the resin composition arranged in the resin coating layer or the internal voids does not contain inorganic particles. <2> According to the invention, there is provided a carrier for developing electrostatic images, in which adhesion of the carrier for developing electrostatic images to an image holder is suppressed when images with high image density are continuously formed over a long period of time under high temperature and high humidity conditions, compared to when area ratio A is less than 10% or exceeds 50%, or area ratio A≦area ratio B. <3> According to the invention, there is provided a carrier for developing electrostatic images in which adhesion of the carrier for developing electrostatic images to an image holder is suppressed when images with high image density are continuously formed over a long period of time under high temperature and high humidity conditions, compared to when area ratio B is less than 0.05 times or more than 0.3 times area ratio A. <4> According to the present invention, there is provided a carrier for developing electrostatic images in which adhesion of the carrier for developing electrostatic images to an image holder is suppressed when images with high image density are continuously formed over a long period of time under high temperature and high humidity conditions, compared to when the internal porosity of the magnetic particles is less than 2% or exceeds 10%. <5> According to the present invention, there is provided a carrier for developing electrostatic images which is less susceptible to adhesion of the carrier for developing electrostatic images to an image holder when images with high image density are continuously formed over a long period of time under high temperature and high humidity conditions, compared to when the number average particle size of the inorganic particles is less than 5 nm or exceeds 90 nm. <6> According to the present invention, there is provided a carrier for developing electrostatic images which suppresses image density fluctuations when images with high image density are continuously formed over a long period of time under high temperature and high humidity conditions, compared to when the inorganic particles consist only of alumina particles. <7> , <8> , <9> or <10> According to the invention, there is provided an electrostatic image developer, process cartridge, image forming apparatus, or image forming method in which adhesion of the electrostatic image developing carrier to the image holder is suppressed when images with high image density are continuously formed over a long period of time under high temperature and high humidity conditions, compared to the case in which a resin composition arranged in a resin coating layer or internal voids is used as a carrier for electrostatic image development that does not contain inorganic particles. [Brief description of the drawings]

[0008] [Figure 1]FIG. 1 is a schematic diagram for explaining a method for confirming internal voids in magnetic particles. [Diagram 2] 1 is a schematic configuration diagram illustrating an example of an image forming apparatus according to an embodiment of the present invention. [Diagram 3] FIG. 2 is a schematic diagram illustrating an example of a process cartridge that is detachably mounted to the image forming apparatus according to the present embodiment. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0009] Hereinafter, embodiments of the present disclosure will be described. These descriptions and examples are merely illustrative of the embodiments, and are not intended to limit the scope of the embodiments.

[0010] In the present disclosure, a numerical range indicated using "~" indicates a range that includes the numerical values ​​before and after "~" as the minimum and maximum values, respectively.

[0011] In the numerical ranges described in the present disclosure in stages, the upper or lower limit value described in one numerical range may be replaced with the upper or lower limit value of another numerical range described in stages. In addition, in the numerical ranges described in the present disclosure, the upper or lower limit value of the numerical range may be replaced with a value shown in the examples.

[0012] In the present disclosure, the term "step" includes not only an independent step, but also a step that cannot be clearly distinguished from other steps, as long as the intended purpose of the step is achieved.

[0013] When an embodiment of the present disclosure is described with reference to the drawings, the configuration of the embodiment is not limited to the configuration shown in the drawings. In addition, the size of the members in each drawing is conceptual, and the relative relationship between the sizes of the members is not limited to this.

[0014] In the present disclosure, each component may contain multiple types of corresponding substances. When referring to the amount of each component in a composition in the present disclosure, if multiple substances corresponding to each component are present in the composition, the total amount of the multiple substances present in the composition is meant unless otherwise specified.

[0015] In the present disclosure, the particles corresponding to each component may include multiple types. When multiple types of particles corresponding to each component are present in the composition, the particle size of each component means the value for a mixture of the multiple types of particles present in the composition, unless otherwise specified.

[0016] In the present disclosure, "(meth)acrylic" means at least one of acrylic and methacrylic, and "(meth)acrylate" means at least one of acrylate and methacrylate.

[0017] In this disclosure, "toner for developing electrostatic images" is also referred to as "toner", "carrier for developing electrostatic images" is also referred to as "carrier", and "electrostatic image developer" is also referred to as "developer".

[0018] [Electrostatic image developing carrier] The carrier for developing electrostatic images according to this embodiment comprises magnetic particles having internal voids, a resin coating layer that coats the magnetic particles and contains a resin and inorganic particles, and a resin composition that is disposed in at least a portion of the internal voids and contains a resin and inorganic particles. Hereinafter, the resin composition that is disposed in the internal voids of the magnetic particles and contains inorganic particles and a resin is also referred to as the "specific resin composition."

[0019] In this embodiment, the resin coating layer contains inorganic particles, and the specific resin composition is disposed in the internal voids of the magnetic particles, so that adhesion of the electrostatic image developing carrier to the image holder is suppressed when high density images are continuously formed over a long period of time under high temperature and high humidity conditions. The reason for this is unclear, but is presumed to be as follows.

[0020] When images with high image density are continuously formed over a long period of time, a large mechanical load is applied to the carrier due to stirring in the developing device, which may cause peeling of the resin coating layer, cracking, chipping, etc. of the magnetic particles. When peeling of the resin coating layer, cracking, chipping, etc. of the magnetic particles occurs, the magnetic particles become exposed, which makes it easy for charge injection into the carrier to occur, particularly under high temperature and high humidity conditions (for example, in an environment of 28°C and 85% RH), and the carrier becomes more likely to adhere to the image holder due to being charged.

[0021] In contrast, in this embodiment, in addition to the inorganic particles being contained in the resin coating layer, the resin and the inorganic particles also penetrate into the internal voids of the magnetic particles and exist as a specific resin composition within the internal voids. Therefore, the filler effect of the inorganic particles contained in the resin coating layer increases the hardness of the resin coating layer, improving its strength, and the anchor effect of the specific resin composition that has entered the internal voids increases the adhesion of the resin coating layer, improving the strength of the magnetic particles themselves. It is presumed that the suppression of peeling of the resin coating layer, cracking, chipping, etc. of the magnetic particles suppresses charge injection under high temperature and high humidity conditions due to exposure of the magnetic particles, and suppresses adhesion to the image holder caused by the carrier being charged.

[0022] For the above reasons, in this embodiment, adhesion of the electrostatic image developing carrier to the image holder is suppressed when high-density images are continuously formed over a long period of time under high-temperature and high-humidity conditions. The carrier according to this embodiment will be described in detail below.

[0023] <Magnetic particles> There are no limitations on the magnetic particles as long as they are magnetic particles having internal voids. Specific examples of the magnetic particles include particles of magnetic oxides such as ferrite, magnetite, etc. The magnetic particles are preferably particles of magnetic oxides, and more preferably ferrite particles.

[0024] From the viewpoint of suppressing adhesion of the carrier to the image carrier, the internal porosity of the magnetic particles is preferably from 2% to 10%, more preferably from 2% to 8%, and even more preferably from 3% to 6%. When the internal porosity of the magnetic particles is equal to or greater than the above lower limit, it is believed that the anchor effect of the specific resin composition is easily obtained, peeling of the resin coating layer, cracking and chipping of the magnetic particles, etc. are suppressed, and adhesion of the carrier to the image holder is suppressed. Furthermore, by keeping the internal porosity of the magnetic particles at or below the upper limit, the magnetic particles are less likely to crack or chip due to mechanical load, and adhesion of the carrier to the image carrier caused thereby is thought to be suppressed. When the magnetic particles are ferrite particles, the internal porosity of the magnetic particles can be adjusted to the above range by controlling the oxygen concentration and the firing temperature during firing. Specifically, the internal porosity can be increased by increasing the oxygen concentration or decreasing the firing temperature.

[0025] Whether or not the magnetic particles have internal voids and the internal void ratio of the magnetic particles are confirmed as follows. First, the carrier is embedded in an embedding agent such as epoxy resin to obtain an embedded product, and then the surface of the embedded product is cut with a diamond knife or the like. The cutting is continued until a sufficient cross section of the magnetic particles is secured to obtain a measurement sample, and the cross section is photographed. The cross section may be photographed by a conventionally known method such as a scanning electron microscope (SEM). Next, a cross section of one magnetic particle is analyzed using a conventionally known image analysis software (for example, WinRoof (Mitani Corporation)). Specifically, as shown in Fig. 1, a gap (i.e., a space where no magnetic particle components exist) present in a square 220 having two opposing vertices, 218a and 218b, which are 3 / 4 of the radius from the center 216 of the circumscribing circle 212 on one diameter 214 of the circumscribing circle 212 of the particle in the cross section 210 of the magnetic particle, is confirmed.

[0026] Whether or not the magnetic particles have internal voids is confirmed by analyzing the cross sections of 100 magnetic particles and confirming whether or not voids exist within the squares 220. In the SEM image of the cross section of the magnetic particle, the voids appear as black regions. When it is confirmed that voids exist within the squares 220 in the cross sections of 90 or more magnetic particles, the magnetic particles are deemed to have internal voids. The internal porosity (%) of a magnetic particle is calculated using the following formula: In the formula, SH is the total area of ​​voids present in the square 220 of 100 magnetic particles, and ST is the total area of ​​the square 220 of 100 magnetic particles. Formula: Internal porosity (%)=(SH / ST)×100 The diameter 214 at any position of the circumscribing circle 212 of the magnetic particle is selected on the cross section 210 of the magnetic particle. The cross section 210 of the magnetic particle to be measured is preferably a cross section cut near the center of the magnetic particle.

[0027] The number-average particle diameter of the magnetic particles is preferably 15 μm or more and 100 μm or less, more preferably 20 μm or more and 80 μm or less, and even more preferably 30 μm or more and 60 μm or less, from the viewpoints of obtaining an appropriate adhesive force between the toner and the carrier, obtaining a sufficient amount of toner development, and obtaining an appropriate magnetic brush and forming an image with excellent fine line reproducibility. The number-average particle size of the magnetic particles is determined by analyzing the cross sections of 100 magnetic particles in the same manner as in the above-mentioned method for confirming internal voids in the magnetic particles. Specifically, the circle-equivalent diameter of the cross section 210 of each particle is determined, and the average value for the 100 particles is taken as the number-average particle size of the magnetic particles.

[0028] The magnetic force of the magnetic particles is preferably 50 emu / g or more, more preferably 60 emu / g or more, in terms of saturation magnetization in a magnetic field of 3000 oersteds. The saturation magnetization is measured using a vibrating sample magnetic measuring device VSMP10-15 (manufactured by Toei Kogyo Co., Ltd.). The measurement sample is packed in a cell with an inner diameter of 7 mm and a height of 5 mm and set in the device. The measurement is performed by applying a magnetic field and sweeping up to a maximum of 3000 oersteds. The applied magnetic field is then reduced, and a hysteresis curve is prepared on a recording paper. The saturation magnetization, residual magnetization, and retentivity are determined from the curve data.

[0029] The volume resistivity of magnetic particles is 1×10 5 Ω cm or more 1×10 9 Ω cm or less is preferable, and 1×10 7 Ω cm or more 1×10 9 Ω·cm or less is more preferable. The volume resistivity (Ω·cm) of magnetic particles is measured as follows: 2 The object to be measured is placed flat on the surface of the circular jig on which the electrode plate is arranged, with a thickness of 1 mm to 3 mm, to form a layer. 2 The layer is sandwiched between two electrode plates. In order to eliminate any gaps between the objects being measured, a 4 kg load is placed on the electrode plates placed on the layer, and then the layer thickness (cm) is measured. Both electrodes above and below the layer are connected to an electrometer and a high-voltage power supply generator. A high voltage is applied to both electrodes so that the electric field is 103.8 V / cm, and the current value (A) that flows at this time is read. The measurement environment is a temperature of 20°C and a relative humidity of 50%. The formula for calculating the volumetric electrical resistivity (Ω·cm) of the object being measured is as shown below. R = E × 20 / (II 0 ) / L In the above formula, R is the volume resistivity of the object to be measured (Ω cm), E is the applied voltage (V), I is the current value (A), and I 0 is the current value (A) at an applied voltage of 0 V, and L is the layer thickness (cm). The coefficient 20 is the area of ​​the electrode plate (cm 2 )

[0030] <Specific resin composition and resin coating layer> The resin coating layer coats the surfaces of the magnetic particles. The resin coating layer may coat at least a portion of the surfaces of the magnetic particles. The resin coating layer may coat only a portion of the surfaces of the magnetic particles, leaving some areas where the surfaces of the magnetic particles are exposed, or it may coat the entire surfaces of the magnetic particles. The specific resin composition is disposed in at least a part of the internal voids of the magnetic particles. The magnetic particles need only have internal voids in which the specific resin composition is disposed, and may further have internal voids in which the specific resin composition is not disposed. Examples of internal voids in which the specific resin composition is not disposed include internal voids in which only resin is disposed, internal voids in which only inorganic particles are disposed, and internal voids in which neither resin nor inorganic particles are disposed. The specific resin composition is preferably a resin and inorganic particles contained in the resin coating layer that coats the surface of the magnetic particles, which penetrate into the internal voids of the magnetic particles. It is more preferable that the specific resin composition present in the internal voids of the magnetic particles and the resin coating layer that coats the surface of the magnetic particles are connected. By connecting the specific resin composition and the resin coating layer, peeling of the resin coating layer is further suppressed, and adhesion of the carrier to the image carrier is suppressed.

[0031] Confirmation that the specific resin composition is disposed in the internal voids of the magnetic particles is performed by observing and analyzing the cross section of the magnetic particles in the same manner as the confirmation method for the internal voids in the magnetic particles described above. For example, when the inorganic particles are silica, elemental analysis is performed on the cross section of the internal voids of the magnetic particles by energy dispersive X-ray spectroscopy (EDX), and the area where silica is present is confirmed by mapping the area where silicon is present, and the area where resin is present is confirmed by mapping the area where carbon is present. Note that confirmation is performed by mapping the elements contained in the inorganic particles, such as mapping the area where aluminum element is present when the inorganic particles are alumina, or the area where calcium element is present when the inorganic particles are calcium carbonate. Whether the specific resin composition is connected to the resin coating layer is also confirmed by observing the cross section of the carrier, in the same manner as for confirming that the specific resin composition is disposed in the internal voids of the magnetic particles.

[0032] Both the specific resin composition and the resin coating layer contain at least inorganic particles and a resin, and may further contain other components. The inorganic particles contained in the specific resin composition and the inorganic particles contained in the resin coating layer are preferably the same type. Specifically, the specific resin composition and the resin coating layer preferably contain inorganic particles having the same material and surface treatment method. In addition, the resin contained in the specific resin composition and the resin contained in the resin coating layer are preferably the same type. Specifically, the specific resin composition and the resin coating layer preferably contain resins having the same main skeleton. The specific resin composition and the inorganic particles, resin, and other components contained in the resin coating layer will be described below.

[0033] (Inorganic particles) Examples of inorganic particles contained in the specific resin composition and the resin coating layer include metal oxide particles such as silica, alumina, titanium oxide (titania), barium titanate, magnesium titanate, calcium titanate, strontium titanate, iron oxide, copper oxide, zinc oxide, tin oxide, chromium oxide, cerium oxide, antimony trioxide, magnesium oxide, zirconium oxide, barium sulfate, barium carbonate, and calcium carbonate; metal compound particles such as barium sulfate, aluminum borate, and potassium titanate; and metal particles such as gold, silver, and copper. In this embodiment, carbon black is not an inorganic particle. The inorganic particles may be composed of only one type of inorganic particles, or may be composed of two or more types of inorganic particles. Among these, the inorganic particles contained in the specific resin composition and the resin coating layer preferably contain silica particles. That is, it is preferable that both the inorganic particles contained in the specific resin composition and the inorganic particles contained in the resin coating layer contain silica. By containing silica particles as the inorganic particles contained in the specific resin composition and the resin coating layer, the fluctuation of image density is suppressed when images with high image density are continuously formed for a long period of time under high temperature and high humidity. Although the reason is unclear, it is assumed that the specific resin composition and the resin coating layer contain silica particles, which makes it easier to maintain the charging characteristics of the carrier.

[0034] The surfaces of the inorganic particles contained in the specific resin composition and the resin coating layer may be hydrophobized. When the inorganic particles contained in the specific resin composition and the resin coating layer contain silica, examples of the hydrophobizing agent include known organosilicon compounds having an alkyl group (e.g., methyl group, ethyl group, propyl group, butyl group, etc.), and specific examples include alkoxysilane compounds, siloxane compounds, and silazane compounds. Among these, the hydrophobizing agent is preferably a silazane compound, and hexamethyldisilazane is preferred. The hydrophobizing agent may be used alone or in combination of two or more. It is believed that the hydrophobization treatment makes it easier for the inorganic particles to be uniformly dispersed in the resin composition, thereby improving the filler effect and making it easier to obtain the anchor effect.

[0035] Examples of methods for hydrophobizing inorganic particles with a hydrophobizing agent include a method in which supercritical carbon dioxide is used to dissolve the hydrophobizing agent in supercritical carbon dioxide and adhere the hydrophobizing agent to the surfaces of the inorganic particles; a method in which a solution containing a hydrophobizing agent and a solvent that dissolves the hydrophobizing agent is applied (e.g., sprayed or coated) to the surfaces of inorganic particles in the atmosphere to adhere the hydrophobizing agent to the surfaces of the inorganic particles; and a method in which a solution containing a hydrophobizing agent and a solvent that dissolves the hydrophobizing agent is added to an inorganic particle dispersion in the atmosphere, the solution is maintained, and then the mixed solution of the inorganic particle dispersion and the solution is dried.

[0036] The number average particle size of the inorganic particles contained in the specific resin composition and the resin coating layer is preferably 5 nm to 90 nm, more preferably 5 nm to 50 nm, and even more preferably 7 nm to 50 nm, from the viewpoint of suppressing carrier adhesion. It is considered that by having the number-average particle diameter of the inorganic particles be equal to or greater than the lower limit, the filler effect by the inorganic particles contained in the resin coating layer and the anchor effect by the inorganic particles contained in the specific resin composition are easily obtained, and adhesion of the carrier to the image carrier is suppressed. Also, by having the number-average particle diameter of the inorganic particles be equal to or less than the upper limit, the inorganic particles easily enter the internal voids of the magnetic particles, and the anchor effect by the inorganic particles that have entered the internal voids is easily obtained, and adhesion of the carrier to the image carrier is suppressed. The number-average particle size of the inorganic particles contained in the specific resin composition and the resin coating layer is determined by analyzing the cross section of the carrier in the same manner as the above-mentioned method for confirming the internal voids in the magnetic particles. Specifically, the number-average particle size of the inorganic particles is determined by averaging the circle-equivalent diameters of each of a total of 100 inorganic particles present in the internal voids of the magnetic particles and the resin coating layer. Preferably, the observation and analysis are performed using a field emission scanning electron microscope (FE-SEM) capable of high-resolution imaging. Specific examples of FE-SEM include Hitachi High-Tech's Regulus series "SU8010", "Regulus8100", "Regulus8220", "Regulus8230", "Regulus8240", and "ULTRA55", and JEOL's "JSM-IT800". The number average particle size of the inorganic particles contained in the specific resin composition and the resin coating layer may be the number average particle size of the inorganic particles measured with a laser diffraction / scattering type particle size distribution measuring device.

[0037] The amount of inorganic particles contained in the specific resin composition is preferably such that the ratio of the total area of ​​the inorganic particles contained in the specific resin composition to the total area of ​​the specific resin composition in the cross section of the specific resin composition (hereinafter also referred to as "area ratio B") is 0.5% to 15%. The area ratio B is more preferably 1% to 12%, and even more preferably 2% to 10%. It is considered that the area ratio B is equal to or greater than the lower limit, and thus the inorganic particles contained in the specific resin composition can easily provide the anchoring effect, thereby suppressing adhesion of the carrier to the image carrier. Also, it is considered that the area ratio B is equal to or less than the upper limit, and thus the elasticity of the resin contained in the specific resin composition can easily alleviate mechanical loads, thereby suppressing cracking, chipping, etc. of the magnetic particles, thereby suppressing adhesion of the carrier to the image carrier. The area ratio B is determined by analyzing the cross sections of 100 particles of the specific resin composition contained in the internal voids of the magnetic particles in the same manner as in the above-mentioned method for confirming that the specific resin composition is disposed in the internal voids of the magnetic particles. Specifically, the total area of ​​the specific resin composition and the total area of ​​the regions of the inorganic particles contained in the specific resin composition are determined for the 100 particles of the specific resin composition to calculate the area ratio B.

[0038] The amount of inorganic particles contained in the resin coating layer is preferably such that the ratio of the total area of ​​the inorganic particles contained in the resin coating layer to the total area of ​​the resin coating layer in the cross section of the resin coating layer (hereinafter also referred to as "area ratio A") is 10% or more and 50% or less. Moreover, the area ratio A is more preferably 20% or more and 45% or less, and further preferably 25% or more and 40% or less. It is considered that the area ratio A is equal to or greater than the lower limit, and thus the filler effect of the inorganic particles contained in the resin coating layer is easily obtained, and adhesion of the carrier to the image carrier is suppressed. Also, it is considered that the area ratio A is equal to or less than the upper limit, and thus the strength of the resin coating layer is improved by the binding force of the resin contained in a large amount in the resin coating layer, and peeling of the resin coating layer is suppressed, and adhesion of the carrier to the image carrier is suppressed. The area ratio A is determined by analyzing the cross sections of 100 carriers in the same manner as in the above-mentioned method for confirming internal voids in magnetic particles. Specifically, in the resin coating layer on the cross section of each particle, the total area of ​​the resin coating layer and the total area of ​​the inorganic particle region contained in the resin coating layer are determined to calculate the area ratio A.

[0039] From the viewpoint of suppressing adhesion of the carrier to the image carrier, it is preferable that the above-mentioned area ratio A and area ratio B satisfy the relationship of area ratio A>area ratio B. In particular, from the viewpoint of suppressing adhesion of the carrier to the image carrier, it is more preferable that the area ratio A is in the above-mentioned range and that the area ratio A>area ratio B. By making the area ratio A>area ratio B, the filler effect of the inorganic particles contained in the resin coating layer is obtained, while the decrease in the anchor effect caused by the resin of the specific resin composition being too small in the internal voids of the magnetic particles is suppressed. In other words, it is considered that both the filler effect and the anchor effect are obtained efficiently, and the adhesion of the carrier to the image holder is suppressed.

[0040] From the viewpoint of suppressing adhesion of the carrier to the image carrier, the area ratio B is preferably 0.05 times or more and 0.3 times or less than the area ratio A. In other words, the value of the area ratio B / area ratio A is preferably 0.05 times or more and 0.3 times or less. The value of the area ratio B / area ratio A is more preferably 0.0.7 times or more and 0.25 times or less, and even more preferably 0.1 times or more and 0.2 times or less. When the value of the area ratio B / area ratio A is equal to or more than the lower limit, the anchor effect of the inorganic particles contained in the specific resin composition is easily obtained, and adhesion of the carrier to the image carrier is considered to be suppressed. In addition, when the value of the area ratio B / area ratio A is equal to or less than the upper limit, the decrease in the anchor effect due to the resin of the specific resin composition entering the internal voids of the magnetic particles being too small is suppressed, and adhesion of the carrier to the image carrier is considered to be suppressed.

[0041] (resin) Examples of resins contained in the specific resin composition and the resin coating layer include styrene-acrylic acid copolymers; polyolefin resins such as polyethylene and polypropylene; polyvinyl or polyvinylidene resins such as polystyrene, (meth)acrylic resin, polyacrylonitrile, polyvinyl acetate, polyvinyl alcohol, polyvinyl butyral, polyvinyl chloride, polyvinyl carbazole, polyvinyl ether, and polyvinyl ketone; vinyl chloride-vinyl acetate copolymers; straight silicone resins or modified products thereof consisting of organosiloxane bonds; fluororesins such as polytetrafluoroethylene, polyvinyl fluoride, polyvinylidene fluoride, and polychlorotrifluoroethylene; polyesters; polyurethanes; polycarbonates; amino resins such as urea-formaldehyde resins; and epoxy resins. In particular, from the viewpoint of increasing the affinity with inorganic particles and making it easier to obtain the filler effect and anchor effect, it is preferable that the resin contained in the specific resin composition and the resin coating layer contains a (meth)acrylic resin, it is more preferable that the resin contains 50 mass% or more of (meth)acrylic resin, based on the total mass of the resin in the specific resin composition and the resin coating layer, and it is particularly preferable that the resin contains 80 mass% or more of (meth)acrylic resin, based on the total mass of the resin in the specific resin composition and the resin coating layer.

[0042] The specific resin composition and the resin coating layer preferably contain a (meth)acrylic resin having an alicyclic structure, from the viewpoint of increasing the affinity with inorganic particles, obtaining the filler effect and anchor effect, and particularly obtaining high hardness. The (meth)acrylic resin having an alicyclic structure contains at least a polymerization component having an alicyclic structure as a polymerization component. Among the polymerization components of the (meth)acrylic resin having an alicyclic structure, the polymerization component having an alicyclic structure includes an alicyclic alkyl ester of (meth)acrylic acid (for example, an ester of (meth)acrylic acid and an alcohol having an alicyclic structure with a carbon number of 3 to 9), and specifically includes cyclohexyl (meth)acrylate, etc. The (meth)acrylic resin having an alicyclic structure may be a copolymer of a polymerization component having an alicyclic structure and a polymerization component not having an alicyclic structure. As the polymerization component not having an alicyclic structure, a lower alkyl ester of (meth)acrylic acid (for example, a (meth)acrylic acid alkyl ester having an alkyl group with 1 to 9 carbon atoms) is preferable, and specific examples thereof include methyl (meth)acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, butyl (meth)acrylate, hexyl (meth)acrylate, and 2-ethylhexyl (meth)acrylate. These monomers may be used alone or in combination of two or more.

[0043] The (meth)acrylic resin having an alicyclic structure preferably contains cyclohexyl (meth)acrylate as a polymerization component. The content of the monomer unit derived from cyclohexyl (meth)acrylate contained in the (meth)acrylic resin having an alicyclic structure is preferably 75% by mass or more and 100% by mass or less, more preferably 85% by mass or more and 100% by mass or less, and even more preferably 95% by mass or more and 100% by mass or less, based on the total mass of the (meth)acrylic resin having an alicyclic structure.

[0044] From the viewpoint of adhesion to magnetic particles, the weight average molecular weight of the resin contained in the specific resin composition and the resin coating layer is preferably less than 300,000, more preferably less than 250,000, even more preferably 5,000 or more and less than 250,000, and particularly preferably 10,000 or more and 200,000 or less. Here, the weight average molecular weight is measured by gel permeation chromatography (GPC). The molecular weight measurement by GPC was performed using a Tosoh GPC HLC-8120 as the measuring device, a Tosoh TSKgel SuperHM-M (15 cm) column, and THF solvent. The weight average molecular weight was calculated from the measurement results using a molecular weight calibration curve prepared with monodisperse polystyrene standard samples.

[0045] (Other ingredients) The specific resin composition and the resin coating layer may further contain, in addition to the inorganic particles and the resin, other components such as conductive particles, nitrogen-containing resin particles, etc. The conductivity of the conductive particles is defined as a volume resistivity of 1×10 at 20° C. 7 This means that the resistance is less than Ω cm. Examples of the conductive particles include carbon black, as well as inorganic particles other than carbon black that have conductivity (for example, titanium oxide, tin oxide). Examples of nitrogen-containing resin particles include particles of (meth)acrylic resins obtained by polymerizing dimethylaminoethyl (meth)acrylate, dimethylacrylamide, acrylonitrile, etc.; amino resins such as urea, melamine, guanamine, aniline, etc.; amide resins; urethane resins; and copolymers of the above resins.

[0046] (Arrangement of specific resin composition and formation of resin coating layer) The method of disposing the specific resin composition in the internal voids of the magnetic particles and forming a resin coating layer on the surface of the magnetic particles is not particularly limited, and examples thereof include a method of using a resin liquid in which resin, inorganic particles, and other components used as necessary are dissolved or dispersed in a solvent. Specifically, for example, a method of using a first resin liquid in which the concentrations of inorganic particles and resin are both low, mixing the first resin liquid with the magnetic particles, and then adding and mixing a second resin liquid in which the concentrations of inorganic particles and resin are both higher than the first resin liquid can be mentioned. In this method, the inorganic particles and resin are likely to enter the internal voids of the magnetic particles in the process of mixing the first resin liquid with the magnetic particles, and then the resin coating layer is likely to be formed in the process of adding and mixing the second resin liquid. Therefore, it is easy to obtain a carrier in which the specific resin composition is disposed in the internal voids of the magnetic particles and a resin coating layer is formed on the surface of the magnetic particles. Below, as an example of a method for disposing a specific resin composition and forming a resin coating layer, a method having a first step of mixing a first resin liquid with magnetic particles and a second step of adding a second resin liquid to the mixture of the first resin liquid and magnetic particles and further mixing will be described.

[0047] As described above, the first resin liquid and the second resin liquid are prepared by dissolving or dispersing the resin, inorganic particles, and other components used as necessary in a solvent. The solvent is not particularly limited, and examples of the solvent that can be used include aromatic hydrocarbons such as toluene and xylene, ketones such as acetone and methyl ethyl ketone, ethers such as tetrahydrofuran and dioxane, etc. The solvent contained in the first resin liquid and the solvent contained in the second resin liquid may be the same or different, and are preferably the same.

[0048] The concentration of the inorganic particles in the first resin liquid is, for example, in the range of 0.05% by mass to 10% by mass, preferably 0.07% by mass to 5% by mass, and more preferably 0.1% by mass to 3% by mass. The concentration of the inorganic particles in the second resin liquid is, for example, in the range of 1% by mass to 20% by mass, preferably 2% by mass to 15% by mass, and more preferably 3% by mass to 10% by mass. The concentration of the inorganic particles in the first resin liquid is preferably in the range of 0.01 to 0.8 times the concentration of the inorganic particles in the second resin liquid, more preferably in the range of 0.02 to 0.6 times, and even more preferably in the range of 0.03 to 0.4 times.

[0049] The resin concentration in the first resin liquid is, for example, in the range of 0.5% by mass to 20% by mass, preferably 1% by mass to 15% by mass, and more preferably 2% by mass to 10% by mass. The resin concentration in the second resin liquid is, for example, in the range of 3% by mass to 30% by mass, preferably 4% by mass to 25% by mass, and more preferably 5% by mass to 20% by mass. The resin concentration in the first resin liquid is preferably in the range of 0.1 to 0.9 times the resin concentration in the second resin liquid, more preferably in the range of 0.2 to 0.8 times, and even more preferably in the range of 0.3 to 0.7 times.

[0050] The viscosity of the first resin liquid at 25° C. is, for example, in the range of 5 mPa·s to 50 mPa·s, preferably 10 mPa·s to 40 mPa·s, and more preferably 12 mPa·s to 30 mPa·s. The viscosity of the second resin liquid at 25° C. is, for example, in the range of 30 mPa·s to 120 mPa·s, preferably 35 mPa·s to 100 mPa·s, and more preferably 40 mPa·s to 80 mPa·s. The viscosity of the first resin liquid at 25°C is preferably in the range of 0.05 to 0.6 times the viscosity of the second resin liquid at 25°C, more preferably in the range of 0.1 to 0.5 times, and even more preferably in the range of 0.2 to 0.4 times. The viscosity of the resin liquid at 25° C. is measured as follows: Specifically, a vibration type viscometer is used and the measurement is performed by immersing a detection terminal in the resin liquid.

[0051] The conditions for the first step include, for example, a temperature of 30° C. to 70° C., a time of 10 minutes to 60 minutes, and a pressure (gauge pressure) of −30 kPa to 0 kPa. The conditions for the second step include, for example, a temperature of 70° C. or higher and 90° C. or lower, a time of 10 minutes or higher and 120 minutes or lower, and a pressure (gauge pressure) of −95 kPa or higher and −70 kPa or lower. The method having the first and second steps may further include other steps as necessary, such as a step of removing the solvent after the second step, and a step of removing fine powder and coarse powder of the obtained particles.

[0052] From the viewpoint of suppressing concentration fluctuation over time, the average thickness of the resin coating layer in the obtained carrier is preferably 0.6 μm or more and 1.4 μm or less, more preferably 0.8 μm or more and 1.2 μm or less, and particularly preferably 0.8 μm or more and 1.1 μm or less. The average thickness of the resin coating layer is determined by analyzing the cross sections of 100 carriers in the same manner as the method for confirming the internal voids in the magnetic particles described above. Specifically, the thickness of the resin coating layer is determined at nine points on the cross section of each particle, and the average of all the thicknesses at each of the nine points for the 100 particles is taken as the average thickness of the resin coating layer.

[0053] The exposed area ratio of the magnetic particles on the carrier surface is preferably 5% to 30%, more preferably 7% to 25%, and even more preferably 10% to 25%. The exposed area ratio of the magnetic particles on the carrier can be controlled by the amount of resin used to form the resin coating layer, and the greater the amount of resin relative to the amount of magnetic particles, the smaller the exposed area ratio.

[0054] The exposed area ratio of the magnetic particles on the carrier surface is a value determined by the following method. A target carrier and magnetic particles from which the resin coating layer has been removed from the target carrier are prepared. Methods for removing the resin coating layer from the carrier include, for example, a method for removing the resin coating layer by dissolving the resin component with an organic solvent, and a method for removing the resin coating layer by eliminating the resin component by heating at about 800°C. The carrier and magnetic particles are each used as measurement samples, and the Fe concentration (atomic%) on the sample surface is quantified by XPS, and the exposed area ratio (%) of the magnetic particles is calculated by (Fe concentration of the carrier)÷(Fe concentration of the magnetic particles)×100.

[0055] The number average particle diameter of the carrier is preferably 15 μm or more and 100 μm or less, more preferably 20 μm or more and 80 μm or less, and particularly preferably 25 μm or more and 40 μm or less, from the viewpoints of obtaining an appropriate adhesive force between the toner and the carrier, obtaining a sufficient amount of toner development, obtaining an appropriate magnetic brush, and forming an image with excellent fine line reproducibility. The number average particle diameter of the carrier is determined in the same manner as the number average particle diameter of the magnetic particles described above.

[0056] [Electrostatic image developer] The developer according to the present embodiment is a two-component developer containing the electrostatic image developing carrier according to the present embodiment and a toner. The toner contains toner particles and, if necessary, an external additive.

[0057] The mixture ratio (mass ratio) of the carrier to the toner in the developer is preferably from 100:1 to 100:15, more preferably from 100:4 to 100:12.

[0058] <Toner particles> The toner particles are configured to contain, for example, a binder resin, and, if necessary, a colorant, a release agent, and other additives.

[0059] -Binding resin- Examples of the binder resin include vinyl resins made of homopolymers of monomers such as styrenes (e.g., styrene, parachlorostyrene, α-methylstyrene, etc.), (meth)acrylic acid esters (e.g., methyl acrylate, ethyl acrylate, n-propyl acrylate, n-butyl acrylate, lauryl acrylate, 2-ethylhexyl acrylate, methyl methacrylate, ethyl methacrylate, n-propyl methacrylate, lauryl methacrylate, 2-ethylhexyl methacrylate, etc.), ethylenically unsaturated nitriles (e.g., acrylonitrile, methacrylonitrile, etc.), vinyl ethers (e.g., vinyl methyl ether, vinyl isobutyl ether, etc.), vinyl ketones (e.g., vinyl methyl ketone, vinyl ethyl ketone, vinyl isopropenyl ketone, etc.), and olefins (e.g., ethylene, propylene, butadiene, etc.), or copolymers of two or more of these monomers. Examples of the binder resin include non-vinyl resins such as epoxy resins, polyester resins, polyurethane resins, polyamide resins, cellulose resins, polyether resins, and modified rosin, mixtures of these with the vinyl resins, and graft polymers obtained by polymerizing vinyl monomers in the coexistence of these. These binder resins may be used alone or in combination of two or more kinds.

[0060] The binder resin is preferably a polyester resin. The polyester resin may be, for example, a known amorphous polyester resin. The polyester resin may be used in combination with a crystalline polyester resin together with the amorphous polyester resin. However, the content of the crystalline polyester resin is preferably in the range of 2% by mass to 40% by mass (preferably 2% by mass to 20% by mass) based on the total binder resin.

[0061] The "crystallinity" of a resin refers to the presence of a clear endothermic peak rather than a stepwise change in the amount of endothermic heat in differential scanning calorimetry (DSC); specifically, it refers to the half-width of the endothermic peak being within 10°C when measured at a heating rate of 10 (°C / min). On the other hand, the term "amorphous" for a resin refers to a half-width exceeding 10° C., a stepwise change in endothermic heat quantity, or no clear endothermic peak being observed.

[0062] Amorphous polyester resin The amorphous polyester resin may be, for example, a condensation polymer of a polyvalent carboxylic acid and a polyhydric alcohol. As the amorphous polyester resin, a commercially available product or a synthesized product may be used.

[0063] Examples of polyvalent carboxylic acids include aliphatic dicarboxylic acids (e.g., oxalic acid, malonic acid, maleic acid, fumaric acid, citraconic acid, itaconic acid, glutaconic acid, succinic acid, alkenylsuccinic acid, adipic acid, sebacic acid, etc.), alicyclic dicarboxylic acids (e.g., cyclohexanedicarboxylic acid, etc.), aromatic dicarboxylic acids (e.g., terephthalic acid, isophthalic acid, phthalic acid, naphthalenedicarboxylic acid, etc.), anhydrides thereof, and lower alkyl esters thereof (e.g., having 1 to 5 carbon atoms). Among these, aromatic dicarboxylic acids are preferable as polyvalent carboxylic acids. The polyvalent carboxylic acid may be a trivalent or higher carboxylic acid having a crosslinked or branched structure in combination with a dicarboxylic acid. Examples of the trivalent or higher carboxylic acid include trimellitic acid, pyromellitic acid, anhydrides thereof, and lower (e.g., carbon number 1 to 5) alkyl esters thereof. The polyvalent carboxylic acids may be used alone or in combination of two or more kinds.

[0064] Examples of polyhydric alcohols include aliphatic diols (e.g., ethylene glycol, diethylene glycol, triethylene glycol, propylene glycol, butanediol, hexanediol, neopentyl glycol, etc.), alicyclic diols (e.g., cyclohexanediol, cyclohexanedimethanol, hydrogenated bisphenol A, etc.), and aromatic diols (e.g., ethylene oxide adducts of bisphenol A, propylene oxide adducts of bisphenol A, etc.). Among these, examples of polyhydric alcohols include aromatic diols and alicyclic diols, and more preferably aromatic diols. As the polyhydric alcohol, a polyhydric alcohol having a crosslinked or branched structure of three or more may be used in combination with the diol. Examples of the polyhydric alcohol having a trihydric or higher valence include glycerin, trimethylolpropane, and pentaerythritol. The polyhydric alcohols may be used alone or in combination of two or more kinds.

[0065] The glass transition temperature (Tg) of the amorphous polyester resin is preferably 50°C or higher and 80°C or lower, and more preferably 50°C or higher and 65°C or lower. The glass transition temperature is determined from a DSC curve obtained by differential scanning calorimetry (DSC), and more specifically, it is determined from the "extrapolated glass transition onset temperature" described in the method for determining glass transition temperature in JIS K7121:1987 "Method for measuring transition temperature of plastics."

[0066] The weight average molecular weight (Mw) of the amorphous polyester resin is preferably 5,000 or more and 1,000,000 or less, and more preferably 7,000 or more and 500,000 or less. The number average molecular weight (Mn) of the amorphous polyester resin is preferably 2,000 or more and 100,000 or less. The molecular weight distribution Mw / Mn of the amorphous polyester resin is preferably 1.5 or more and 100 or less, and more preferably 2 or more and 60 or less. The weight average molecular weight and number average molecular weight are measured by gel permeation chromatography (GPC). The molecular weight measurement by GPC is performed using a Tosoh GPC HLC-8120GPC as the measuring device, a Tosoh TSKgel SuperHM-M (15 cm) column, and THF solvent. The weight average molecular weight and number average molecular weight are calculated from the measurement results using a molecular weight calibration curve created with a monodisperse polystyrene standard sample.

[0067] The amorphous polyester resin can be obtained by a known production method, for example, by carrying out the reaction while removing water and alcohol generated during condensation by setting the polymerization temperature to 180° C. or higher and 230° C. or lower, and reducing the pressure in the reaction system as necessary. If the raw material monomer is not soluble or compatible at the reaction temperature, a high boiling point solvent may be added as a solubilizing agent to dissolve it. In this case, the polycondensation reaction is carried out while distilling off the solubilizing agent. If a monomer with poor compatibility is present in the copolymerization reaction, it is recommended that the monomer with poor compatibility is condensed in advance with the acid or alcohol to be polycondensed, and then polycondensed with the main component.

[0068] Crystalline polyester resin The crystalline polyester resin may be, for example, a polycondensate of a polyvalent carboxylic acid and a polyhydric alcohol. As the crystalline polyester resin, a commercially available product or a synthesized product may be used. Here, the crystalline polyester resin is preferably a polycondensate using a straight-chain aliphatic polymerizable monomer rather than a polymerizable monomer having an aromatic ring, since it easily forms a crystalline structure.

[0069] Examples of polyvalent carboxylic acids include aliphatic dicarboxylic acids (e.g., oxalic acid, succinic acid, glutaric acid, adipic acid, suberic acid, azelaic acid, sebacic acid, 1,9-nonanedicarboxylic acid, 1,10-decanedicarboxylic acid, 1,12-dodecanedicarboxylic acid, 1,14-tetradecanedicarboxylic acid, 1,18-octadecanedicarboxylic acid, etc.), aromatic dicarboxylic acids (e.g., dibasic acids such as phthalic acid, isophthalic acid, terephthalic acid, naphthalene-2,6-dicarboxylic acid, etc.), anhydrides thereof, and lower alkyl esters thereof (e.g., having 1 to 5 carbon atoms). The polyvalent carboxylic acid may be a trivalent or higher carboxylic acid having a crosslinked or branched structure in combination with a dicarboxylic acid. Examples of the trivalent carboxylic acid include aromatic carboxylic acids (e.g., 1,2,3-benzenetricarboxylic acid, 1,2,4-benzenetricarboxylic acid, 1,2,4-naphthalenetricarboxylic acid, etc.), their anhydrides, and their lower alkyl esters (e.g., carbon number 1 to 5). As the polybasic carboxylic acid, a dicarboxylic acid having a sulfonic acid group and a dicarboxylic acid having an ethylenic double bond may be used in combination with these dicarboxylic acids. The polyvalent carboxylic acids may be used alone or in combination of two or more kinds.

[0070] Examples of polyhydric alcohols include aliphatic diols (for example, straight-chain aliphatic diols having 7 to 20 carbon atoms in the main chain). Examples of aliphatic diols include ethylene glycol, 1,3-propanediol, 1,4-butanediol, 1,5-pentanediol, 1,6-hexanediol, 1,7-heptanediol, 1,8-octanediol, 1,9-nonanediol, 1,10-decanediol, 1,11-undecanediol, 1,12-dodecanediol, 1,13-tridecanediol, 1,14-tetradecanediol, 1,18-octadecanediol, and 1,14-eicosanedecanediol. Among these, 1,8-octanediol, 1,9-nonanediol, and 1,10-decanediol are preferred as aliphatic diols. The polyhydric alcohol may be a trihydric or higher alcohol having a crosslinked or branched structure in combination with the diol. Examples of the trihydric or higher alcohol include glycerin, trimethylolethane, trimethylolpropane, and pentaerythritol. The polyhydric alcohols may be used alone or in combination of two or more kinds.

[0071] Here, the polyhydric alcohol has an aliphatic diol content of 80 mol % or more, preferably 90 mol % or more.

[0072] The melting temperature of the crystalline polyester resin is preferably 50°C or higher and 100°C or lower, more preferably 55°C or higher and 90°C or lower, and even more preferably 60°C or higher and 85°C or lower. The melting temperature is determined from a DSC curve obtained by differential scanning calorimetry (DSC) based on the "peak melting temperature" described in the method for determining melting temperature in JIS K7121:1987 "Method for measuring transition temperature of plastics."

[0073] The weight average molecular weight (Mw) of the crystalline polyester resin is preferably 6,000 or more and 35,000 or less.

[0074] The crystalline polyester resin can be obtained, for example, by a known production method, like the amorphous polyester.

[0075] The content of the binder resin is preferably from 40% by mass to 95% by mass, more preferably from 50% by mass to 90% by mass, and even more preferably from 60% by mass to 85% by mass, based on the total mass of the toner particles.

[0076] -Coloring agent- Examples of colorants include carbon black, chrome yellow, Hansa Yellow, benzidine yellow, threne yellow, quinoline yellow, pigment yellow, permanent orange GTR, pyrazolone orange, Balkan orange, watch young red, permanent red, brilliant carmine 3B, brilliant carmine 6B, DuPont oil red, pyrazolone red, lithol red, rhodamine B lake, lake red C, pigment red, rose bengal, aniline blue, Examples of the dyes include pigments such as ultramarine blue, chalcoil blue, methylene blue chloride, phthalocyanine blue, pigment blue, phthalocyanine green, and malachite green oxalate; and dyes such as acridine-based, xanthene-based, azo-based, benzoquinone-based, azine-based, anthraquinone-based, thioindigo-based, dioxazine-based, thiazine-based, azomethine-based, indigo-based, phthalocyanine-based, aniline black-based, polymethine-based, triphenylmethane-based, diphenylmethane-based, and thiazole-based dyes. The colorant may be used alone or in combination of two or more kinds.

[0077] The colorant may be surface-treated as necessary, or may be used in combination with a dispersant. In addition, a plurality of types of colorants may be used in combination.

[0078] The content of the colorant is preferably from 1% by mass to 30% by mass, and more preferably from 3% by mass to 15% by mass, based on the total mass of the toner particles.

[0079] -Release agent- Examples of the release agent include hydrocarbon waxes, natural waxes such as carnauba wax, rice wax, and candelilla wax, synthetic or mineral / petroleum waxes such as montan wax, and ester waxes such as fatty acid esters and montan acid esters. The release agent is not limited to these.

[0080] The melting temperature of the release agent is preferably 50°C or higher and 110°C or lower, and more preferably 60°C or higher and 100°C or lower. The melting temperature is determined from a DSC curve obtained by differential scanning calorimetry (DSC) based on the "peak melting temperature" described in the method for determining melting temperature in JIS K7121:1987 "Method for measuring transition temperature of plastics."

[0081] The content of the release agent is preferably from 1% by mass to 20% by mass, and more preferably from 5% by mass to 15% by mass, based on the total mass of the toner particles.

[0082] -Other additives- Examples of other additives include known additives such as magnetic materials, charge control agents, inorganic powders, etc. These additives are contained in the toner particles as internal additives.

[0083] -Characteristics of toner particles, etc.- The toner particles may be toner particles having a single layer structure, or may be toner particles having a so-called core-shell structure composed of a core portion (core particle) and a coating layer (shell layer) that coats the core portion. The toner particles having a core-shell structure may be composed of, for example, a core containing a binder resin and, if necessary, other additives such as a colorant and a release agent, and a coating layer containing the binder resin.

[0084] The volume average particle size (D50v) of the toner particles is preferably from 2 μm to 10 μm, and more preferably from 4 μm to 8 μm. The volume average particle size (D50v) of the toner particles is measured using a Coulter Multisizer II (manufactured by Beckman Coulter, Inc.), and the electrolyte is measured using an ISOTON-II (manufactured by Beckman Coulter, Inc.). For the measurement, 0.5 mg to 50 mg of the measurement sample is added to 2 ml of a 5 mass % aqueous solution of a surfactant (preferably sodium alkylbenzene sulfonate) as a dispersant, and this is then added to 100 ml to 150 ml of the electrolyte. The electrolyte with the sample suspended in it is dispersed for 1 minute using an ultrasonic disperser, and the particle size distribution of particles with diameters in the range of 2 μm to 60 μm is measured using a Coulter Multisizer II with an aperture diameter of 100 μm. The number of particles sampled is 50,000. The particle size distribution based on volume is plotted from the smallest diameter side, and the particle size at which the cumulative 50% is reached is defined as the volume average particle size D50v.

[0085] The average circularity of the toner particles is preferably 0.94 or more and 1.00 or less, and more preferably 0.95 or more and 0.98 or less. The average circularity of toner particles is calculated by (circular equivalent perimeter) / (perimeter) [(perimeter of a circle having the same projected area as the particle image) / (perimeter of the particle projected image)]. Specifically, it is a value measured by the following method. First, the toner particles to be measured are sucked and collected, flattened, and a still image of the particles is captured by instantaneous strobe light emission, and the particle image is analyzed by a flow-type particle image analyzer (FPIA-3000 manufactured by Sysmex Corporation). The number of samples to be taken in order to calculate the average circularity is 3,500. When the toner contains an external additive, the toner (developer) to be measured is dispersed in water containing a surfactant, and then ultrasonic treatment is performed to obtain toner particles from which the external additive has been removed.

[0086] -Method of manufacturing toner particles- The toner particles may be produced by any of a dry production method (e.g., a kneading and pulverizing method, etc.) and a wet production method (e.g., an aggregation and coalescence method, a suspension polymerization method, a dissolution suspension method, etc.). There is no particular limitation on these production methods, and any known production method may be used. Among these, it is preferable to obtain the toner particles by the aggregation and coalescence method.

[0087] Specifically, for example, when toner particles are produced by the aggregation and coalescence method, the toner particles are produced through a step of preparing a resin particle dispersion in which resin particles to be a binder resin are dispersed (resin particle dispersion preparation step), a step of aggregating resin particles (other particles, if necessary) in the resin particle dispersion (in a dispersion after mixing other particle dispersions, if necessary) to form aggregated particles (aggregated particle formation step), and a step of heating the aggregated particle dispersion in which the aggregated particles are dispersed, to fuse and coalesce the aggregated particles, thereby forming toner particles (fusion and coalescence step).

[0088] Each step will be described in detail below. In the following description, a method for obtaining toner particles containing a colorant and a release agent will be described, but the colorant and the release agent are used as necessary. Of course, additives other than the colorant and the release agent may be used.

[0089] -Resin particle dispersion preparation process- Along with a resin particle dispersion in which resin particles serving as a binder resin are dispersed, for example, a colorant particle dispersion in which colorant particles are dispersed, and a release agent particle dispersion in which release agent particles are dispersed are prepared.

[0090] The resin particle dispersion liquid is prepared, for example, by dispersing resin particles in a dispersion medium with the aid of a surfactant.

[0091] The dispersion medium used in the resin particle dispersion liquid is, for example, an aqueous medium. Examples of the aqueous medium include water such as distilled water and ion-exchanged water, alcohols, etc. These may be used alone or in combination of two or more kinds.

[0092] Examples of the surfactant include anionic surfactants such as sulfate salts, sulfonates, phosphates, and soaps; cationic surfactants such as amine salts and quaternary ammonium salts; and nonionic surfactants such as polyethylene glycols, alkylphenol ethylene oxide adducts, and polyhydric alcohols. Among these, anionic surfactants and cationic surfactants are particularly preferred. The nonionic surfactants may be used in combination with anionic surfactants or cationic surfactants. The surfactant may be used alone or in combination of two or more kinds.

[0093] In the resin particle dispersion, the resin particles are dispersed in the dispersion medium by a general dispersion method such as a rotary shear type homogenizer, a ball mill having a media, a sand mill, or a dyno mill. Depending on the type of resin particles, the resin particles may be dispersed in the dispersion medium by a phase inversion emulsification method. The phase inversion emulsification method is a method in which the resin to be dispersed is dissolved in a hydrophobic organic solvent in which the resin is soluble, a base is added to the organic continuous phase (O phase) to neutralize it, and then an aqueous medium (W phase) is added to invert the phase from W / O to O / W, thereby dispersing the resin in the aqueous medium in the form of particles.

[0094] The volume average particle size of the resin particles dispersed in the resin particle dispersion is, for example, preferably from 0.01 μm to 1 μm, more preferably from 0.08 μm to 0.8 μm, and even more preferably from 0.1 μm to 0.6 μm. The volume average particle size of the resin particles is measured by using a particle size distribution obtained by measurement using a laser diffraction particle size distribution measuring device (for example, LA-700 manufactured by Horiba, Ltd.), subtracting the cumulative distribution from the small particle size side for the volume of the divided particle size range (channel), and measuring the particle size at which the cumulative distribution is 50% of all particles as the volume average particle size D50v. The volume average particle sizes of particles in other dispersions are measured in the same manner.

[0095] The content of the resin particles in the resin particle dispersion is preferably from 5% by mass to 50% by mass, and more preferably from 10% by mass to 40% by mass.

[0096] In the same manner as the resin particle dispersion liquid, for example, a colorant particle dispersion liquid and a release agent particle dispersion liquid are also prepared. That is, the volume average particle size, dispersion medium, dispersion method, and particle content of the particles in the resin particle dispersion liquid are the same for the colorant particles dispersed in the colorant particle dispersion liquid and the release agent particles dispersed in the release agent particle dispersion liquid.

[0097] -Agglomerated particle formation process- Next, the resin particle dispersion liquid, the colorant particle dispersion liquid, and the release agent particle dispersion liquid are mixed together. Then, in the mixed dispersion, the resin particles, the colorant particles, and the release agent particles are hetero-aggregated to form aggregated particles containing the resin particles, the colorant particles, and the release agent particles and having a diameter close to that of the target toner particles.

[0098] Specifically, for example, an aggregating agent is added to the mixed dispersion, the pH of the mixed dispersion is adjusted to be acidic (e.g., pH 2 or more and 5 or less), a dispersion stabilizer is added as necessary, and then the mixed dispersion is heated to a temperature close to the glass transition temperature of the resin particles (specifically, for example, glass transition temperature of the resin particles -30°C or more and glass transition temperature -10°C or less), and the particles dispersed in the mixed dispersion are aggregated to form aggregated particles. In the aggregated particle formation process, for example, the mixed dispersion may be stirred with a rotary shear homogenizer, an aggregating agent may be added at room temperature (e.g., 25°C), the pH of the mixed dispersion may be adjusted to an acidic state (e.g., pH 2 or more and 5 or less), a dispersion stabilizer may be added as necessary, and then the mixture may be heated.

[0099] Examples of the flocculant include a surfactant having a polarity opposite to that of the surfactant contained in the mixed dispersion, an inorganic metal salt, and a divalent or higher metal complex. When a metal complex is used as the flocculant, the amount of the surfactant used is reduced, and the charging characteristics are improved. If necessary, an additive that forms a complex or a similar bond with the metal ion of the flocculant may be used together with the flocculant. As this additive, a chelating agent is preferably used.

[0100] Examples of inorganic metal salts include metal salts such as calcium chloride, calcium nitrate, barium chloride, magnesium chloride, zinc chloride, aluminum chloride, and aluminum sulfate; and inorganic metal salt polymers such as polyaluminum chloride, polyaluminum hydroxide, and calcium polysulfide. The chelating agent may be a water-soluble chelating agent, for example, oxycarboxylic acid such as tartaric acid, citric acid, gluconic acid, etc., aminocarboxylic acid such as iminodiacetic acid (IDA), nitrilotriacetic acid (NTA), ethylenediaminetetraacetic acid (EDTA), etc. The amount of the chelating agent added is preferably 0.01 parts by mass or more and 5.0 parts by mass or less, and more preferably 0.1 parts by mass or more and less than 3.0 parts by mass, based on 100 parts by mass of the resin particles.

[0101] -Fusion / unification process- Next, the aggregated particle dispersion liquid in which the aggregated particles are dispersed is heated, for example, to a temperature equal to or higher than the glass transition temperature of the resin particles (for example, a temperature 10° C. to 30° C. higher than the glass transition temperature of the resin particles) to fuse and coalesce the aggregated particles to form toner particles.

[0102] Through the above steps, toner particles are obtained. After obtaining the aggregated particle dispersion in which the aggregated particles are dispersed, the aggregated particle dispersion and the resin particle dispersion in which the resin particles are dispersed are further mixed together to aggregate the aggregated particles so that the resin particles are further attached to the surfaces of the aggregated particles, thereby forming second aggregated particles; and the second aggregated particle dispersion in which the second aggregated particles are dispersed is heated to fuse and coalesce the second aggregated particles, thereby forming toner particles having a core-shell structure.

[0103] After the fusion and coalescence process is completed, the toner particles formed in the solution are subjected to a known washing process, solid-liquid separation process, and drying process to obtain dried toner particles. From the viewpoint of chargeability, the washing process is preferably performed by sufficient substitution washing with ion-exchanged water. From the viewpoint of productivity, the solid-liquid separation process is preferably performed by suction filtration, pressure filtration, etc. From the viewpoint of productivity, the drying process is preferably performed by freeze drying, air flow drying, fluidized drying, vibration type fluidized drying, etc.

[0104] The toner according to the present embodiment is produced, for example, by adding an external additive to the obtained toner particles in a dry state and mixing them. The mixing may be performed, for example, by using a V blender, a Henschel mixer, a Loedige mixer, etc. Furthermore, if necessary, coarse particles of the toner may be removed using a vibration sieve, an air sieve, etc.

[0105] -External additives- The external additive may be, for example, inorganic particles. Examples of the inorganic particles include SiO 2 , TiO 2 , Al 2 O 3 , CuO, ZnO, SnO 2 , CEO 2 , Fe 2 O 3 , MgO, BaO, CaO, K 2 O, Na 2 O, ZrO 2 , CaO SiO 2 , K 2 O (TiO 2 ) n , Al 2 O 3 2SiO 2 , CaCO 3 , MgCO 3 , BaSO 4 , MgSO 4 etc.

[0106] The surface of the inorganic particles as an external additive may be subjected to a hydrophobic treatment. The hydrophobic treatment may be performed, for example, by immersing the inorganic particles in a hydrophobic treatment agent. The hydrophobic treatment agent is not particularly limited, and examples thereof include silane coupling agents, silicone oils, titanate coupling agents, and aluminum coupling agents. These may be used alone or in combination of two or more. The amount of the hydrophobizing agent is usually, for example, 1 part by mass or more and 10 parts by mass or less with respect to 100 parts by mass of the inorganic particles.

[0107] Examples of external additives include resin particles (resin particles such as polystyrene, polymethyl methacrylate, and melamine resin), cleaning agents (for example, metal salts of higher fatty acids such as zinc stearate, and fluorine-based polymer particles), and the like.

[0108] The amount of the external additive is preferably from 0.01% by mass to 5% by mass, and more preferably from 0.01% by mass to 2.0% by mass, based on the toner particles.

[0109] [Image forming device, image forming method] The image forming apparatus according to the present embodiment includes an image carrier, a charging device for charging the surface of the image carrier, an electrostatic image forming device for forming an electrostatic image on the surface of the charged image carrier, a developing device for containing an electrostatic image developer and developing the electrostatic image formed on the surface of the image carrier as a toner image with the electrostatic image developer, a transfer device for transferring the toner image formed on the surface of the image carrier to the surface of a recording medium, and a fixing device for fixing the toner image transferred to the surface of the recording medium. The electrostatic image developer according to the present embodiment is used as the electrostatic image developer.

[0110] In the image forming apparatus according to this embodiment, an image forming method (the image forming method according to this embodiment) is carried out, which includes a charging step of charging the surface of an image carrier, an electrostatic image forming step of forming an electrostatic image on the surface of the charged image carrier, a developing step of developing the electrostatic image formed on the surface of the image carrier as a toner image using the electrostatic image developer according to this embodiment, a transfer step of transferring the toner image formed on the surface of the image carrier to the surface of a recording medium, and a fixing step of fixing the toner image transferred to the surface of the recording medium.

[0111] The image forming apparatus according to the present embodiment may be any of known image forming apparatuses, such as a direct transfer type apparatus in which a toner image formed on the surface of an image holder is directly transferred to a recording medium; an intermediate transfer type apparatus in which a toner image formed on the surface of an image holder is primarily transferred to the surface of an intermediate transfer body, and the toner image transferred to the surface of the intermediate transfer body is secondarily transferred to the surface of a recording medium; a cleaning device provided with a cleaning means for cleaning the surface of the image holder after the transfer of the toner image and before charging; and a static elimination device provided with a static elimination means for irradiating the surface of the image holder with static elimination light to eliminate static electricity after the transfer of the toner image and before charging. When the image forming apparatus according to the present embodiment is an intermediate transfer type apparatus, the transfer device is configured to have, for example, an intermediate transfer body to whose surface a toner image is transferred, a primary transfer device which primarily transfers the toner image formed on the surface of the image carrier onto the surface of the intermediate transfer body, and a secondary transfer device which secondarily transfers the toner image transferred onto the surface of the intermediate transfer body onto the surface of a recording medium.

[0112] In the image forming apparatus according to the present embodiment, for example, a portion including the developing device may have a cartridge structure (process cartridge) that is detachably attached to the image forming apparatus. As the process cartridge, for example, a process cartridge that contains the electrostatic charge image developer according to the present embodiment and is equipped with the developing device is preferably used.

[0113] An example of an image forming apparatus according to the present embodiment will be described below, but the present invention is not limited to this example. In the following description, the main parts shown in the drawings will be described, and the description of the rest will be omitted.

[0114] FIG. 2 is a schematic diagram showing the configuration of the image forming apparatus according to the present embodiment. The image forming apparatus shown in Fig. 2 includes first to fourth image forming units 10Y, 10M, 10C, and 10K (image forming means) of an electrophotographic type that output images of the respective colors of yellow (Y), magenta (M), cyan (C), and black (K) based on color-separated image data. These image forming units (hereinafter sometimes simply referred to as "units") 10Y, 10M, 10C, and 10K are arranged in parallel at predetermined distances from each other in the horizontal direction. These units 10Y, 10M, 10C, and 10K may be process cartridges that are detachably attached to the image forming apparatus.

[0115] Above each of the units 10Y, 10M, 10C, and 10K, an intermediate transfer belt (one example of an intermediate transfer body) 20 is provided, which extends through each unit. The intermediate transfer belt 20 is provided wrapped around a drive roll 22 and a support roll 24, and runs in a direction from the first unit 10Y toward the fourth unit 10K. A force is applied to the support roll 24 by a spring (not shown) or the like in a direction away from the drive roll 22, and tension is applied to the intermediate transfer belt 20 wrapped around them. An intermediate transfer body cleaning device 30 is provided on the image carrier side of the intermediate transfer belt 20, facing the drive roll 22. The developing devices 4Y, 4M, 4C, and 4K of the units 10Y, 10M, 10C, and 10K are supplied with yellow, magenta, cyan, and black toners contained in toner cartridges 8Y, 8M, 8C, and 8K, respectively.

[0116] Since the first to fourth units 10Y, 10M, 10C, and 10K have the same configuration and operation, the first unit 10Y that forms a yellow image and is disposed upstream in the direction in which the intermediate transfer belt travels will be described here as a representative.

[0117] The first unit 10Y has a photoconductor 1Y that acts as an image carrier. Around the photoconductor 1Y, a charging roll (an example of a charging device) 2Y that charges the surface of the photoconductor 1Y to a predetermined potential, an exposure device (an example of an electrostatic image forming device) 3 that exposes the charged surface to a laser beam 3Y based on a color-separated image signal to form an electrostatic image, a developing device 4Y that supplies charged toner to the electrostatic image to develop it, a primary transfer roll 5Y (an example of a primary transfer device) that transfers the developed toner image onto an intermediate transfer belt 20, and a photoconductor cleaning device (an example of a cleaning device) 6Y that removes toner remaining on the surface of the photoconductor 1Y after the primary transfer are arranged in this order. The primary transfer roll 5Y is disposed inside the intermediate transfer belt 20, and is provided at a position facing the photoconductor 1Y. A bias power supply (not shown) that applies a primary transfer bias is connected to the primary transfer rolls 5Y, 5M, 5C, and 5K of each unit. Each bias power supply changes the value of the transfer bias applied to each primary transfer roll under the control of a control unit (not shown).

[0118] Hereinafter, the operation of forming a yellow image in the first unit 10Y will be described. First, prior to operation, the surface of the photoconductor 1Y is charged to a potential of −600V to −800V by the charging roll 2Y. The photoconductor 1Y has a conductivity (for example, a volume resistivity of 1×10 at 20° C. -6 The photosensitive layer is formed by laminating a photosensitive layer on a substrate having a resistivity of Ωcm or less. This photosensitive layer is usually highly resistive (the resistance of ordinary resins), but when irradiated with a laser beam, the resistivity of the portion irradiated with the laser beam changes. Therefore, the exposed surface of the charged photoreceptor 1Y is irradiated with a laser beam 3Y from the exposure device 3 in accordance with image data for yellow sent from a control unit (not shown). As a result, an electrostatic charge image of a yellow image pattern is formed on the surface of the photoreceptor 1Y.

[0119] An electrostatic image is an image formed on the surface of the photoconductor 1Y by electrostatic charging. The laser beam 3Y reduces the resistivity of the irradiated parts of the photosensitive layer, causing the charged charges on the surface of the photoconductor 1Y to flow, while the charges remain in the parts not irradiated by the laser beam 3Y. This is a so-called negative latent image. The electrostatic image formed on the photoconductor 1Y rotates to a predetermined developing position as the photoconductor 1Y travels. At this developing position, the electrostatic image on the photoconductor 1Y is developed into a toner image by the developing device 4Y and made visible.

[0120] The developing device 4Y contains an electrostatic image developer including at least yellow toner and a carrier, for example. The yellow toner is triboelectrically charged by being stirred inside the developing device 4Y, and is held on a developer roll (an example of a developer holder) with a charge of the same polarity (negative polarity) as the charge on the photoconductor 1Y. As the surface of the photoconductor 1Y passes through the developing device 4Y, the yellow toner electrostatically adheres to the discharged latent image portion on the surface of the photoconductor 1Y, and the latent image is developed with the yellow toner. The photoconductor 1Y on which the yellow toner image has been formed continues to travel at a predetermined speed, and the toner image developed on the photoconductor 1Y is transported to a predetermined primary transfer position.

[0121] When the yellow toner image on the photoreceptor 1Y is transported to the primary transfer position, a primary transfer bias is applied to the primary transfer roll 5Y, and an electrostatic force from the photoreceptor 1Y toward the primary transfer roll 5Y acts on the toner image, and the toner image on the photoreceptor 1Y is transferred onto the intermediate transfer belt 20. The transfer bias applied at this time has a polarity (+) opposite to the polarity (-) of the toner, and is controlled to, for example, +10 μA by a control unit (not shown) in the first unit 10Y. On the other hand, the toner remaining on the photoconductor 1Y is removed and collected by the photoconductor cleaning device 6Y.

[0122] The primary transfer bias applied to the primary transfer rolls 5M, 5C, and 5K subsequent to the second unit 10M is also controlled in accordance with the first unit. In this manner, the intermediate transfer belt 20 onto which the yellow toner image has been transferred by the first unit 10Y is conveyed successively through the second to fourth units 10M, 10C, and 10K, where the toner images of each color are transferred and superimposed.

[0123] The intermediate transfer belt 20 onto which the four color toner images have been transferred in multiple layers through the first to fourth units reaches a secondary transfer section that is composed of the intermediate transfer belt 20, a support roll 24 that contacts the inner surface of the intermediate transfer belt, and a secondary transfer roll (an example of a secondary transfer device) 26 arranged on the image bearing surface side of the intermediate transfer belt 20. Meanwhile, a recording paper (an example of a recording medium) P is fed at a predetermined timing into the gap between the secondary transfer roll 26 and the intermediate transfer belt 20 via a supply mechanism, and a secondary transfer bias is applied to the support roll 24. The transfer bias applied at this time has a (-) polarity that is the same as the (-) polarity of the toner, and an electrostatic force from the intermediate transfer belt 20 toward the recording paper P acts on the toner image, and the toner image on the intermediate transfer belt 20 is transferred onto the recording paper P. The secondary transfer bias at this time is determined according to the resistance detected by a resistance detection means (not shown) that detects the resistance of the secondary transfer section, and is voltage-controlled.

[0124] Thereafter, the recording paper P is sent to a pressure contact portion (nip portion) of a pair of fixing rolls in the fixing device 28, where the toner image is fixed onto the recording paper P, forming a fixed image.

[0125] The recording paper P onto which the toner image is transferred can be, for example, plain paper used in electrophotographic copying machines, printers, etc. In addition to the recording paper P, other examples of the recording medium include overhead projector sheets and the like. To further improve the smoothness of the image surface after fixing, it is preferable that the surface of the recording paper P is also smooth. For example, coated paper in which the surface of ordinary paper is coated with resin or the like, art paper for printing, etc. are preferably used.

[0126] After the color image has been fixed, the recording paper P is conveyed toward the discharge section, and the series of color image forming operations is completed.

[0127] [Process cartridge] The process cartridge according to this embodiment is a process cartridge that contains the electrostatic image developer according to this embodiment and is equipped with a developing device that develops an electrostatic image formed on the surface of an image carrier using the electrostatic image developer into a toner image, and is detachable from an image forming apparatus.

[0128] The process cartridge according to this embodiment is not limited to the above configuration, and may be configured to include a developing device and, as necessary, at least one other device selected from an image carrier, a charging device, an electrostatic image forming device, and a transfer device.

[0129] An example of a process cartridge according to the present embodiment will be described below, but the present invention is not limited to this example. In the following description, the main parts shown in the drawings will be described, and the description of the rest will be omitted.

[0130] FIG. 3 is a schematic diagram showing the process cartridge according to the present embodiment. The process cartridge 200 shown in FIG. 3 is configured, for example, by a housing 117 having a mounting rail 116 and an opening 118 for exposure, in which a photoconductor 107 (an example of an image carrier), a charging roll 108 (an example of a charging device) provided around the photoconductor 107, a developing device 111, and a photoconductor cleaning device 113 (an example of a cleaning device) are integrally combined and held together into a cartridge. In FIG. 3, reference numeral 109 denotes an exposure device (an example of an electrostatic image forming device), 112 denotes a transfer device, 115 denotes a fixing device, and 300 denotes a recording paper (an example of a recording medium). EXAMPLES

[0131] Hereinafter, the embodiments of the present invention will be described in detail with reference to examples, but the embodiments of the present invention are not limited to these examples. In the following description, unless otherwise specified, "parts" and "%" are based on mass.

[0132] [Preparation of ferrite particles] <Preparation of ferrite particles (1)> Fe 2 O 3 1318 parts and Mn(OH) 2 587 parts and Mg(OH) 2 The mixture was mixed with 96 parts of polyvinyl alcohol and 0.5 parts of polycarboxylic acid as a dispersant, and zirconia beads with a media diameter of 1 mm were added to water, and the mixture was ground and mixed in a sand mill to obtain a dispersion. The volume average particle size of the particles in the dispersion was 1.5 μm. The dispersion liquid was used as a raw material to granulate and dry the mixture using a spray dryer, obtaining granules with a volume average particle size of 33 μm. Next, in an oxygen-nitrogen mixed atmosphere with an oxygen partial pressure of 1.3%, firing was performed using an electric furnace at a temperature of 1325°C for 4 hours, and then heating was performed in the air at a temperature of 900°C for 3 hours to obtain fired particles. The fired particles were crushed and classified to obtain ferrite particles (1) with a number average particle size of 31 μm. The obtained ferrite particles (1) had internal voids and had an internal porosity of 6%.

[0133] <Preparation of ferrite particles (2)> Ferrite particles (2) having a number average particle size of 31 μm were obtained in the same manner as ferrite particles (1) except that the oxygen partial pressure during main sintering was 0.5% and the temperature was 1500° C. The obtained ferrite particles (2) had internal voids and an internal porosity of 2%.

[0134] <Preparation of ferrite particles (3)> Ferrite particles (3) having a number average particle size of 31 μm were obtained in the same manner as ferrite particles (1), except that the oxygen partial pressure during main sintering was 1.5% and the temperature was 1200° C. The obtained ferrite particles (3) had internal voids and an internal porosity of 10%.

[0135] <Preparation of ferrite particles (4)> Ferrite particles (4) having a number average particle size of 31 μm were obtained in the same manner as ferrite particles (1), except that the oxygen partial pressure during main sintering was 0.5% and the temperature was 1550° C. The obtained ferrite particles (4) had internal voids and an internal porosity of 1%.

[0136] <Preparation of ferrite particles (5)> Ferrite particles (5) having a number average particle size of μm were obtained in the same manner as ferrite particles (1) except that the oxygen partial pressure during main sintering was 1.6% and the temperature was 1150° C. The obtained ferrite particles (5) had internal voids and an internal porosity of 12%.

[0137] [Preparation of resin liquid] <Preparation of resin liquid (1-1)> Resin: Cyclohexyl methacrylate polymer (weight average molecular weight: 150,000) 5.2 parts Inorganic particles (1): Silica (number average particle size: 12 nm, fumed silica particles surface-treated with hexamethyldisilazane, manufactured by Tokuyama Corporation, product number: HM20S) 0.25 parts Solvent: 100 parts toluene The above materials and glass beads (diameter 1 mm, same amount as toluene) were placed in a sand mill and stirred at a rotation speed of 500 rpm for 30 minutes to obtain a resin liquid (1-1).

[0138] <Preparation of resin liquids (1-2) to (1-15) and resin liquids (2-1) to (2-12)> Resin liquids (1-2) to (1-15) and resin liquids (2-1) to (2-12) were obtained in the same manner as resin liquid (1-1), except that the amount of resin added, the type and amount of inorganic particles added, and the amount of solvent added were changed as shown in Tables 1 to 2. In the table below, inorganic particles (2) to (4) are as follows: In addition, in the table below, "-" indicates that no particles were added. Inorganic particles (2): Alumina (number average particle size: 13 nm, alumina particles surface-treated with octisilane) Inorganic particles (3): Silica (number average particle size: 5 nm, fumed silica particles surface-treated with hexamethyldisilazane) Inorganic particles (4): Silica (number average particle size: 90 nm, fumed silica particles surface-treated with hexamethyldisilazane)

[0139] [Table 1]

[0140] [Table 2]

[0141] [Creating the carrier] <Preparation of carrier (1)> 3000 parts of ferrite particles (1) and 100 parts of resin liquid (1-1) were placed in a vacuum degassing kneader, heated to 50°C at normal pressure, and mixed and stirred for 30 minutes (first step). Then, 730 parts of resin liquid (2-1) were added, heated to 70°C, and stirred at -80kPa (gauge pressure) for 1 hour (second step). Then, the temperature was raised to 80°C and the pressure was reduced to -90kPa (gauge pressure) to distill off toluene. Next, fine and coarse powders were removed using an elbow jet to obtain carrier (1). The average thickness of the resin coating layer in carrier (1) was 1.02 μm.

[0142] When the cross section of the obtained carrier (1) was examined, it was confirmed that the specific resin composition containing silica and resin was arranged in the internal voids of the ferrite particles (1) and that the specific resin composition was connected to the resin coating layer. The results of the area ratio A in the resin coating layer ("A" in the table), the area ratio B in the specific resin composition ("B" in the table), and the value of the area ratio B / area ratio A ("B / A" in the table) obtained by the above-mentioned method are shown in Table 3.

[0143] <Preparation of Carriers (2) to (20)> Carriers (2) to (20) were obtained in the same manner as carrier (1), except that the type of ferrite particles used, the type of resin liquid used in the first step, and the type of resin liquid used in the second step were changed as shown in Table 3. In the following table, "-" for the resin liquid indicates that the step was omitted. The average thicknesses of the resin coating layers in carriers (2) to (20) were 0.97 μm, 1.05 μm, 0.95 μm, 1.05 μm, 1.02 μm, 1.02 μm, 1.02 μm, 1.02 μm, 1 μm, 0.98 μm, 0.95 μm, 1.03 μm, 1.1 μm, 0.98 μm, 1.1 μm, 0.95 μm, 0.93 μm, 1.0 μm, and 1.02 μm, respectively. When the cross sections of the obtained carriers (2) to (15), (18), and (20) were examined, it was confirmed that a specific resin composition containing silica and a resin was disposed in the internal voids of the ferrite particles, and that the specific resin composition was connected to the resin coating layer. On the other hand, when the cross sections of the carriers (16) and (17) were examined, it was confirmed that only a resin was disposed in the internal voids of the ferrite particles. Furthermore, when the cross section of the carrier (19) was examined, it was confirmed that neither a resin nor inorganic particles were disposed in the internal voids of the ferrite particles. For the obtained carrier, the area ratio A in the resin coating layer ("A" in the table), the area ratio B in the specific resin composition ("B" in the table), and the value of area ratio B / area ratio A ("B / A" in the table) were determined using the above-mentioned methods. The results are shown in Table 3.

[0144] [Preparation of developer] Any of the obtained carriers (1) to (20) and a toner obtained by the method described below were placed in a V blender in a mixing ratio of carrier:toner = 100:10 (mass ratio) and stirred for 20 minutes to obtain developers (1) to (20), respectively.

[0145] [evaluation] <Evaluation of Carrier Adhesion> A modified image forming apparatus DocuPrintColor3540 (manufactured by Fujifilm Business Innovation Co., Ltd.) was prepared, and the obtained developer was placed in the developing unit. Under high temperature and high humidity (28°C, 85% RH), 100,000 cyan high image density images (solid images with 100% image density) were continuously formed on A3 size paper, and then an image having two 2 cm x 2 cm patches was formed, after which the apparatus was forcibly stopped. Thereafter, adhesive tape was pressed against the developed portion on the photoreceptor, and the adhesive surface of the tape was observed under an optical microscope, and it was found that the adhesive surface had a density of 1 cm. 2 The number of carrier particles (including crushed fine powder) adhering to the development area was counted. This was done for two development areas on the photoreceptor, and the average value was calculated and evaluated. The evaluation criteria are as follows, with up to G3 being the acceptable level. The results are shown in Table 3 ("Adhesion" in the table).

[0146] -Evaluation criteria- G1: 0~1 pieces G1.5: 2~3 pieces G2: 4~5 pieces G2.5: 6~7 pieces G3: 8~9 pieces G4: 10~11 pieces G5: 12 or more

[0147] <Evaluation of image density> Of the 100,000 solid images formed in the above evaluation of carrier adhesion, the first image and the 100,000th image were each measured at nine points using an image densitometer (X-Rite938, manufactured by X-Rite Corporation) to determine the average density E obtained for each image. The average density E of the first image was designated E1, and the average density E of the 100,000th image was designated E2. The density fluctuation rate was calculated using the following formula and evaluated according to the following evaluation criteria. The results are shown in Table 3 ("Density" in the table). Formula: Decrease rate=|(E1-E2)| / E1

[0148] -Evaluation criteria- G1: Fluctuation rate is less than 0.05 G2: Fluctuation rate is between 0.05 and 0.1 G3: Fluctuation rate is between 0.1 and 0.2

[0149] [Table 3]

[0150] From the above results, it can be seen that in this embodiment, compared to the comparative example, adhesion of carrier to the image carrier is suppressed when high-density images are continuously formed over a long period of time in a high-temperature, high-humidity environment.

[0151] [Toner production] The toner used in the preparation of the developer was obtained by the following method.

[0152] <Preparation of Resin Particle Dispersion (1)> Ethylene glycol (FUJIFILM Wako Pure Chemical Industries, Ltd.) 37 parts Neopentyl glycol (FUJIFILM Wako Pure Chemical Industries, Ltd.) 65 parts 1,9-nonanediol (FUJIFILM Wako Pure Chemical Industries, Ltd.) 32 parts Terephthalic acid (FUJIFILM Wako Pure Chemical Industries, Ltd.) 96 parts The above materials were charged in a flask, and the temperature was raised to 200°C over 1 hour. After confirming that the reaction system was stirred uniformly, 1.2 parts of dibutyltin oxide were added. The temperature was raised to 240°C over 6 hours while distilling off the water produced, and stirring was continued at 240°C for 4 hours to obtain a polyester resin (acid value 9.4 mgKOH / g, weight average molecular weight 13,000, glass transition temperature 62°C). This polyester resin was transferred in a molten state to an emulsifying and dispersing machine (Cavitron CD1010, Eurotech) at a rate of 100 g per minute. Separately, a dilute ammonia water with a concentration of 0.37%, which was obtained by diluting reagent ammonia water with ion-exchanged water, was placed in a tank, and the mixture was transferred to the emulsifying and dispersing machine at a rate of 0.1 liters per minute simultaneously with the polyester resin while being heated to 120°C with a heat exchanger. The emulsifying and dispersing machine was operated at a rotor rotation speed of 60Hz and a pressure of 5kg / cm. 2By operating under the above conditions, a resin particle dispersion (1) having a volume average particle size of 160 nm and a solid content of 30% was obtained.

[0153] <Preparation of Resin Particle Dispersion (2)> Decanedioic acid (Tokyo Chemical Industry Co., Ltd.) 81 parts Hexanediol (FUJIFILM Wako Pure Chemical Industries, Ltd.) 47 parts The above materials were charged into a flask, and the temperature was raised to 160°C over 1 hour. After confirming that the reaction system was stirred uniformly, 0.03 parts of dibutyltin oxide was added. The temperature was raised to 200°C over 6 hours while distilling off the water produced, and stirring was continued at 200°C for 4 hours. The reaction liquid was then cooled, solid-liquid separation was performed, and the solid matter was dried at a temperature of 40°C under reduced pressure to obtain polyester resin (C1) (melting point 64°C, weight average molecular weight 15,000).

[0154] Polyester resin (C1) 50 parts Anionic surfactants (Neogen SC, Daiichi Kogyo Seiyaku Co., Ltd.) 2nd Division 200 parts deionized water The above materials were heated to 120°C and thoroughly dispersed using a homogenizer (Ultra Turrax T50, IKA Co., Ltd.), and then dispersed using a pressure discharge homogenizer. When the volume average particle size reached 180 nm, the particles were collected to obtain a resin particle dispersion (2) with a solid content of 20%.

[0155] <Preparation of Colorant Particle Dispersion (1)> Cyan pigment (Pigment Blue 15:3, Dainichi Seika Color & Chemicals Co., Ltd.) 10 parts Anionic surfactants (Neogen SC, Daiichi Kogyo Seiyaku Co., Ltd.) 2nd Division 80 parts deionized water The above materials were mixed and dispersed for 1 hour using a high-pressure impact disperser (Ultimaizer HJP30006, Sugino Machine Co., Ltd.) to obtain a colorant particle dispersion (1) having a volume average particle size of 180 nm and a solid content of 20%.

[0156] <Preparation of Release Agent Particle Dispersion (1)> Paraffin wax (HNP-9, Nippon Seiro Co., Ltd.) 50 parts Anionic surfactants (Neogen SC, Daiichi Kogyo Seiyaku Co., Ltd.) 2nd Division 200 parts deionized water The above materials were heated to 120°C and thoroughly dispersed using a homogenizer (Ultra Turrax T50, IKA), and then dispersed using a pressure discharge homogenizer. When the volume average particle size reached 200 nm, the particles were collected to obtain a release agent particle dispersion (1) with a solid content of 20%.

[0157] <Preparation of toner particles> ·Resin particle dispersion (1) 150 parts ·Resin particle dispersion (2) 50 parts Colorant particle dispersion (1) 25 parts Release agent particle dispersion (1) 35 parts 0.4 parts polyaluminum chloride 100 parts deionized water The above materials were put into a round stainless steel flask, thoroughly mixed and dispersed using a homogenizer (Ultra Turrax T50, IKA), and then heated to 48 ° C. in a heating oil bath while stirring the flask. After the reaction system was kept at 48 ° C. for 60 minutes, 70 parts of resin particle dispersion (1) were slowly added. Next, the pH was adjusted to 8.0 using a 0.5 mol / L aqueous sodium hydroxide solution, the flask was sealed, the seal of the stirring shaft was magnetically sealed, and the mixture was heated to 90 ° C. while continuing to stir and held for 30 minutes. Next, the mixture was cooled at a temperature drop rate of 5 ° C. / min, solid-liquid separation was performed, and the mixture was thoroughly washed with ion-exchanged water. Next, the solid-liquid separation was performed, and the mixture was redispersed in ion-exchanged water at 30 ° C., and stirred and washed for 15 minutes at a rotation speed of 300 rpm. This washing operation was repeated six more times, and when the pH of the filtrate reached 7.54 and the electrical conductivity reached 6.5 μS / cm, solid-liquid separation was performed, and vacuum drying was continued for 24 hours to obtain toner particles (1) having a volume average particle size of 5.7 μm.

[0158] <External Addition of Toner Particles> 100 parts of the above toner particles (1) and 0.7 parts of hydrophobic silica (RY50 manufactured by Nippon Aerosil Co., Ltd.) were mixed in a Henschel mixer to obtain a toner.

[0159] The present embodiment includes the following aspects. (((1))) Magnetic particles having internal voids; a resin coating layer that coats the magnetic particles and contains a resin and inorganic particles; A resin composition disposed in at least a portion of the internal void and containing a resin and inorganic particles; A carrier for developing electrostatic images comprising: (((2))) The electrostatic image developing carrier according to (((1))), wherein, in a cross section of the resin coating layer, a ratio of a total area of ​​the inorganic particles contained in the resin coating layer to an entire area of ​​the resin coating layer is defined as an area ratio A, and in a cross section of the resin composition, a ratio of a total area of ​​the inorganic particles contained in the resin composition to an entire area of ​​the resin composition is defined as an area ratio B, whereby the area ratio A is 10% or more and 50% or less and area ratio A>area ratio B. (((3))) The electrostatic image developing carrier according to (((2))), wherein the area ratio B is 0.05 to 0.3 times the area ratio A. (((4))) The carrier for developing electrostatic images according to any one of (((1))) to (((3))), wherein the magnetic particles have an internal porosity of 2% or more and 10% or less. (((5))) The carrier for developing electrostatic images according to any one of (((1))) to (((4))), wherein the number average particle size of the inorganic particles is 5 nm or more and 90 nm or less. (((6))) The carrier for developing electrostatic images according to any one of (((1))) to (((5))), wherein the inorganic particles include silica particles. (((7))) a toner for developing an electrostatic image; A carrier for developing an electrostatic image according to any one of (((1))) to (((6))), 13. An electrostatic image developer comprising: (((8))) a developing device that contains the electrostatic image developer according to (((7))) and develops an electrostatic image formed on a surface of an image carrier into a toner image by using the electrostatic image developer, A process cartridge that is detachably attached to an image forming apparatus. (((9))) An image carrier; a charging device for charging the surface of the image carrier; an electrostatic image forming device for forming an electrostatic image on the charged surface of the image carrier; a developing device that contains the electrostatic image developer according to (((7))) and develops the electrostatic image formed on the surface of the image carrier into a toner image by the electrostatic image developer; a transfer device for transferring the toner image formed on the surface of the image carrier to a surface of a recording medium; a fixing device for fixing the toner image transferred onto the surface of the recording medium; An image forming apparatus comprising: (((10))) a charging step of charging a surface of an image carrier; an electrostatic image forming step of forming an electrostatic image on the charged surface of the image carrier; a developing step of developing the electrostatic image formed on the surface of the image carrier into a toner image by using the electrostatic image developer according to (((7))); a transfer step of transferring the toner image formed on the surface of the image carrier onto a surface of a recording medium; a fixing step of fixing the toner image transferred onto the surface of the recording medium; The image forming method according to claim 1,

[0160] According to the invention related to (((1))), there is provided an electrostatic image developing carrier in which adhesion of the electrostatic image developing carrier to an image holder is suppressed when images with high image density are continuously formed over a long period of time under high temperature and high humidity conditions, compared to a case in which the resin composition arranged in the resin coating layer or the internal voids does not contain inorganic particles. According to the invention related to (((2))), there is provided a carrier for developing electrostatic images which is suppressed from adhering to an image holder when images with high image density are continuously formed over a long period of time under high temperature and high humidity conditions, as compared with the case where area ratio A is less than 10% or exceeds 50%, or area ratio A≦area ratio B. According to the invention related to (((3))), there is provided a carrier for developing electrostatic images in which adhesion of the carrier for developing electrostatic images to an image holder is suppressed when images with high image density are continuously formed over a long period of time under high temperature and high humidity conditions, as compared with the case where area ratio B is less than 0.05 times or more than 0.3 times area ratio A. According to the invention related to (((4))), there is provided a carrier for developing electrostatic images which suppresses adhesion of the carrier for developing electrostatic images to an image holder when images with high image density are continuously formed over a long period of time under high temperature and high humidity conditions, compared to when the internal porosity of the magnetic particles is less than 2% or exceeds 10%. According to the invention related to (((5))), there is provided a carrier for developing electrostatic images which is suppressed from adhering to an image holder when images with high image density are continuously formed over a long period of time under high temperature and high humidity conditions, as compared with cases in which the number average particle size of inorganic particles is less than 5 nm or exceeds 90 nm. According to the invention related to (((6))), there is provided a carrier for developing electrostatic images which suppresses fluctuations in image density when images with high image density are continuously formed over a long period of time under high temperature and high humidity conditions, as compared to a case in which the inorganic particles consist only of alumina particles. According to the invention related to (((7))), (((8))), (((9))), or (((10))), there is provided an electrostatic image developer, a process cartridge, an image forming apparatus, or an image forming method in which adhesion of the electrostatic image developing carrier to an image holder is suppressed when images with high image density are continuously formed over a long period of time under high temperature and high humidity conditions, compared to the case in which a carrier for developing electrostatic images in which the resin composition disposed in the resin coating layer or in the internal voids does not contain inorganic particles is used. [Explanation of symbols]

[0161] 1Y, 1M, 1C, 1K Photoconductor (an example of an image carrier) 2Y, 2M, 2C, 2K Charging roll (example of charging device) 3 Exposure device (an example of an electrostatic image forming device) 3Y, 3M, 3C, 3K laser beam 4Y, 4M, 4C, 4K developing device 5Y, 5M, 5C, 5K Primary transfer roll (an example of a primary transfer device) 6Y, 6M, 6C, 6K Photoconductor cleaning device (example of cleaning device) 8Y, 8M, 8C, 8K toner cartridges 10Y, 10M, 10C, 10K Image forming units 20 Intermediate transfer belt (an example of an intermediate transfer body) 22 Driving Roll 24 Support roll 26 Secondary transfer roll (an example of a secondary transfer device) 28 Fixing device 30 Intermediate transfer body cleaning device P Recording paper (an example of a recording medium) 107 Photoconductor (an example of an image carrier) 108 Charging roll (an example of a charging device) 109 Exposure device (an example of an electrostatic image forming device) 111 Developing device 112 Transcription device 113 Photoconductor cleaning device (an example of a cleaning device) 115 Fixing device 116 Mounting Rail 117 Cabinet 118 Exposure Aperture 200 Process Cartridge 210 Cross section of magnetic particle 212 Circumscribing circle of a particle in a cross section 210 of the magnetic particle 214 Diameter of circumscribed circle 212 216 Center of circumscribed circle 212 218a, 218b: Points on the diameter 214 of the circumscribing circle 212 that are 1 / 2 the radius from the center 216 of the circumscribing circle 212 220 A square with points 218a and 218b as two opposite vertices 300 Recording paper (an example of a recording medium)

Claims

1. Magnetic particles having internal voids; a resin coating layer that coats the magnetic particles and contains a resin and inorganic particles; A resin composition disposed in at least a portion of the internal void and containing a resin and inorganic particles; A carrier for developing electrostatic images comprising:

2. 2. The carrier for developing electrostatic images according to claim 1, wherein, in a cross section of the resin coating layer, a ratio of a total area of ​​the inorganic particles contained in the resin coating layer to an entire area of ​​the resin coating layer is defined as an area ratio A, and in a cross section of the resin composition, a ratio of a total area of ​​the inorganic particles contained in the resin composition to an entire area of ​​the resin composition is defined as an area ratio B, where the area ratio A is 10% or more and 50% or less and area ratio A>area ratio B.

3. 3. The carrier for developing an electrostatic image according to claim 2, wherein the area ratio B is 0.05 to 0.3 times the area ratio A.

4. 2. The carrier for developing electrostatic images according to claim 1, wherein the internal porosity of said magnetic particles is from 2% to 10%.

5. 2. The carrier for developing an electrostatic image according to claim 1, wherein the number average particle diameter of the inorganic particles is from 5 nm to 90 nm.

6. 6. The electrostatic image developing carrier according to claim 5, wherein the inorganic particles include silica particles.

7. a toner for developing an electrostatic image; A carrier for developing an electrostatic image according to any one of claims 1 to 6, 13. An electrostatic image developer comprising:

8. a developing device that contains the electrostatic image developer according to claim 7 and develops an electrostatic image formed on a surface of an image carrier into a toner image by using the electrostatic image developer, A process cartridge that is detachably attached to an image forming apparatus.

9. An image carrier; a charging device for charging the surface of the image carrier; an electrostatic image forming device for forming an electrostatic image on the charged surface of the image carrier; a developing device that contains the electrostatic image developer according to claim 7 and develops the electrostatic image formed on the surface of the image carrier into a toner image by the electrostatic image developer; a transfer device for transferring the toner image formed on the surface of the image carrier to a surface of a recording medium; a fixing device for fixing the toner image transferred onto the surface of the recording medium; An image forming apparatus comprising:

10. a charging step of charging a surface of an image carrier; an electrostatic image forming step of forming an electrostatic image on the charged surface of the image carrier; a developing step of developing the electrostatic image formed on the surface of the image carrier into a toner image by using the electrostatic image developer according to claim 7; a transfer step of transferring the toner image formed on the surface of the image carrier onto a surface of a recording medium; a fixing step of fixing the toner image transferred onto the surface of the recording medium; The image forming method according to claim 1,

Citation Information

Patent Citations

  • Electrostatic latent image developing carrier and developer for electrostatic latent image development

    JP2007058124A

  • Carrier core material, carrier for developing electrophotography using the same, and developer for electrophotography

    JP2019061188A